2017
DOI: 10.1039/c6sm01026a
|View full text |Cite
|
Sign up to set email alerts
|

Off-equilibrium surface tension in miscible fluids

Abstract: The interfacial tension between immiscible fluids is responsible for a wealth of every-day phenomena, from the spherical shape of small drops and bubbles to the ability to walk on water of many insects. More than a century ago, physicist and mathematician D. Korteweg postulated the existence of an effective interface tension for miscible fluids, whenever a composition gradient exists, as encountered, e.g., in many flow geometries. In this mini-review, we discuss experimental work performed in the last decades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…Their measurements went beyond confirming Korteweg's theory and showed that EIT is also a function of particle structure (basically size and shape) together with particleparticle and particle-solvent interactions (Truzzolillo et al 2016). Effective interfacial tension is expected to have relevance in many fields starting from material processing to multiphase complex fluid dynamic problems involving droplet and bubbles formation, jetting, coalescence and break-up of droplets (Truzzolillo & Cipelletti 2017). Even though progress has been made on the understanding of the above aspects, transient mechanisms and their effect on the formation of the above flow patterns are still unexplored.…”
Section: Introductionmentioning
confidence: 92%
“…Their measurements went beyond confirming Korteweg's theory and showed that EIT is also a function of particle structure (basically size and shape) together with particleparticle and particle-solvent interactions (Truzzolillo et al 2016). Effective interfacial tension is expected to have relevance in many fields starting from material processing to multiphase complex fluid dynamic problems involving droplet and bubbles formation, jetting, coalescence and break-up of droplets (Truzzolillo & Cipelletti 2017). Even though progress has been made on the understanding of the above aspects, transient mechanisms and their effect on the formation of the above flow patterns are still unexplored.…”
Section: Introductionmentioning
confidence: 92%
“…(1) can only exist transiently, before diffusion or other mixing mechanisms smear out the interface leading to a single, homogeneous phase. Notwithstanding this transient, nonequilibrium character, the effective interfacial tension between miscible fluids plays a key role in a wide range of research fields of both academic and practical interest [19], from geosciences (e.g., in mantle convection, magma fragmentation, and the dynamics of Earth's core [20,21]) to hydrology [22], oil recovery [10], filtration and flow in porous media (e.g., in a chromatography column [23]), fluid removal [24], aquifer and soil remediation [25,26], and the modeling of hydrodynamic instabilities, e.g., in Rayleigh-Taylor [27] and Hele-Shaw [28,29] flows. Very recently, convection induced by Korteweg stresses has been proposed as a new mechanism for self-propulsion of droplets [30] and vesicles [31], demonstrating artificial chemotaxis and opening new scenarios in active matter and drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (205) is identical to the one-component result (92), except for the force term which is now a sum over the individual species. The difference in body force contribution between the global form of the first law of thermodynamics (205) and the mechanical power balance (91) is…”
Section: First Law-energy Balancementioning
confidence: 99%
“…where we have used the definition of the mass averaged body force b (202) and the definition of the in-plane diffusive flux j k (191). With equation (206), the mechanical power balance (91), and assuming the decomposition of total energy e into internal energy u and kinetic energy given in equation (93), the global form of the first law of thermodynamics (205) simplifies to…”
Section: First Law-energy Balancementioning
confidence: 99%